Early discontinuation of dual antiplatelet therapy after PCI in patients at high bleeding risk: an OCT-guided clinical case - A. A. Prokhorikhin; Yu. V. Kukushkina; D. D. Zubarev; A. V. Gorbatykh; K. A. Rzaeva (Translational Medicine, 2026)
Background. Optimizing the duration of dual antiplatelet therapy (DAPT) after percutaneous coronary intervention (PCI) remains challenging, especially in patients with high bleeding risk and diabetes mellitus, where stent thrombosis risk is significantly increased due to delayed endothelialization. Objective. To demonstrate the safety of early DAPT discontinuation based on individual assessment of stent endothelialization using optical coherence tomography (OCT). Materials and Methods. We present a clinical case of a 71-year-old female with type II diabetes, atrial fibrillation (CHA2DS2-VASc score of 6), functional class II exertional angina, and a history of left anterior descending (LAD) artery stenting. Risk stratification indicated a high hemorrhagic status: HAS-BLED score of 3, PRECISE-DAPT score of 17, ARC-HBR score of 2, and a CRUSADE score of 49 (corresponding to an 11.9 % risk of major bleeding). Baseline OCT revealed significant narrowing: the minimal lumen area in the LAD was 3.51 mm² (56 % area stenosis), and 2.08 mm² in the right coronary artery (RCA) (72 % area stenosis). Stenting of LAD and right coronary artery was performed using amphilimus-eluting polymer-free stents. DAPT discontinuation was planned at 1 month contingent on sufficient endothelialization per control OCT. Results. Follow-up OCT at one month demonstrated neointimal coverage of 81.18 % of the struts in the LAD and 95.9 % in the RCA. No evidence of stent thrombosis or restenosis was observed. The patient was transitioned to clopidogrel monotherapy, alongside ongoing anticoagulant therapy for the prevention of thrombotic complications associated with atrial fibrillation. During the one-year follow-up period, no ischemic or hemorrhagic adverse events were registered, and there was no recurrence of angina symptoms. Conclusion. The application of OCT for the evaluation of stent strut endothelialization provides a robust rationale for shortening DAPT duration to 1 month in patients with high hemorrhagic risk. This strategy minimizes bleeding threats without escalating the incidence of ischemic events, even in the presence of concomitant diabetes mellitus and multiple comorbidities.